PI3K/Akt regulates survival during differentiation of human macrophages by maintaining NF‐κB‐dependent expression of antiapoptotic Bcl‐xL. Issue 6 (15th September 2014) - Busca, Aurelia; Saxena, Mansi; Iqbal, Salma; Angel, Jonathan; Kumar, Ashok
Abstract : Survival of macrophages is distinctly regulated during and after differentiation. Abstract : Resistance to apoptosis is an important characteristic that human macrophages acquire during differentiation from monocytes. However, the intracellular mechanisms that mediate the development of resistance are not well understood. We have used M‐CSF‐stimulated primary human monocytes and PMA‐treated THP1 cells to study apoptosis resistance during differentiation of human macrophages. Our results indicate that PI3K/Akt distinctively regulates survival of macrophages during and after differentiation. More specifically, a signaling pathway consisting of PI3K/Akt‐NF‐κB‐Bcl‐xL regulates cell survival during the differentiation process. PI3K/Akt‐mediated activation of NF‐κB plays a key role in survival of differentiating macrophages by specifically sustaining antiapoptotic Bcl‐xL expression. With the use of pharmacological inhibitors and siRNA for Akt and Bcl‐xL, we show that in the absence of Akt‐dependent Bcl‐xL expression during differentiation, cells undergo caspase‐mediated apoptosis. In contrast, in differentiated macrophages, Bcl‐xL expression is independent of PI3K/Akt activation. Taken together, these results suggest that survival of macrophages is distinctly regulated during and after differentiation. Our results also suggest new, potential therapeutic targets to modulate differentiation and survival of this cell type.